Prevalence and characterization of Cryptosporidium in sika deer from Northern China - Tang Yan; Xue Nian-Yu; Gao Yang; Gao Zhen-Qiu; Zhuang Hong-Di; Bao Guang-Rong; Cao Hong-Wei; Liu Jing; Li Jian-Ming; Liu Shuo (Parasite)
Cryptosporidium spp. are important zoonotic parasites that can cause moderate to severe diarrhea in humans and animals. However, the epidemiological data of Cryptosporidium in sika deer in China need to be updated. In this study, a total of 466 fecal samples were collected from sika deer in Shandong, Jilin, Liaoning, and Heilongjiang provinces. Nested PCR was used to amplify the SSU rRNA gene to detect Cryptosporidium spp. The results showed that the overall infection rate of Cryptosporidium spp. was 14.81%, with no significant differences among regions (p = 0.05). The highest infection rate was found in Heilongjiang Province (23.60%) and the lowest in Jilin Province (10.71%). The infection rate in summer (23.61%) seemed higher than that in autumn (13.20%), but the difference was not statistically significant (p = 0.30). Notably, young sika deer showed a significantly higher infection rate (28.21%) compared to adults (10.32%) (p < 0.0001). Sequence analysis identified two Cryptosporidium species/genotypes: Cryptosporidium deer genotype (98.55%) and Cryptosporidium ubiquitum (1.45%). Subtyping revealed that the C. ubiquitum isolate belonged to the zoonotic XIIa subtype. These findings provide new insights into the prevalence and genetic diversity of Cryptosporidium in sika deer and suggest that sika deer may act as a potential reservoir for zoonotic Cryptosporidium transmission.